2012
DOI: 10.1155/2012/590619
|View full text |Cite
|
Sign up to set email alerts
|

Hylastes ater(Curculionidae: Scolytinae) AffectingPinus radiataSeedling Establishment in New Zealand

Abstract: The introduced pine bark beetleHylastes aterhas been present in New Zealand for around 100 years. The beetle has been a minor pest on pines. Research was undertaken to control the pest in the 1950s–1970s, with a biological control agent introduced with limited success. Following a reasonably long period with minimal research attention, renewed interest in developing a better understanding of the pest status was initiated in the mid to late 1990s. Subsequently, a significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Further, there have been no published reports of Hylastes spp. attacking pine seedlings in the United States as reported in New Zealand with H. ater . This suggests that there should be no initial consequences on young stands if landowners were to replant pine seedlings in those harvested plots.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Further, there have been no published reports of Hylastes spp. attacking pine seedlings in the United States as reported in New Zealand with H. ater . This suggests that there should be no initial consequences on young stands if landowners were to replant pine seedlings in those harvested plots.…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, clear-cut treatment had no effect on populations of H. salebrosus and H. tenuis and only a significant effect on H. porculus at some clear-cut sites. Hylastes porculus is reported to have a more northern range, 39 so its activity would 40 This suggests that there should be no initial consequences on young stands if landowners were to replant pine seedlings in those harvested plots.…”
Section: Discussionmentioning
confidence: 99%
“…In its dry granule formulation, it has been recommended by the manufacturers for use against many pests. It was used, for example, against the pine bark beetle Hylaster ater (Paykul) (Scolytinae) which compromised forest regeneration of Pinus radiata D. Don in New Zealand (Reay and Walsh 2002a;Reay et al 2012), but is no longer in operational use (Reay and Walsh 2002b). Other studies have demonstrated the efficacy of carbosulfan against Hylaster ater (Lemp eri ere and Julien 1989; Mrlina et al 1994;Heritage et al 1997) and against the large pine weevil Hylobius abietis (L.) (Lemp eri ere and Julien 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Other common insects with high potential to spread PPC are scarabeid beetles of the genus Melolontha, which can devastate entire young plantations of coniferous species [157]. The regeneration and maturation feeding of Hylastes species (H. ater and Hylastes cunicularius (Erichson, 1836)) occurs around the root collar, killing seedlings, and sometimes destroying whole plantations [86,158]. Moreover, Hylobius spp.…”
Section: Forestsmentioning
confidence: 99%